Cellulose nanocrystals derived from oil palm empty fruit bunch reinforced natural rubber latex nanocomposites - Intan Syahiera, Azli; Afkar Rabbani Hidayatullah, Hipeni; Khairatun Najwa, Mohd Amin (Lembaga Minyak Sawit Malaysia, 2022)
Natural rubber latex (NRL) has long been used in lots of application in elastomer industry. However, finished products may develop pinholes or tear easily while being used. Thus, cellulose nanocrystal (CNC) was used as reinforcing filler in NRL to overcome this problem. CNC from cellulose derived from oil palm empty fruit bunch (EFB) was isolated via sulphuric acid hydrolysis method. The CNC concentration added to the NRL was varied at 1, 3 and 5 wt.%. The effect of CNC addition and curing temperature of 70°C and 100°C of NRL on the mechanical properties, functional group presence, glass transition temperature (Tg) and swelling behaviour of CNC/NRL nanocomposite were studied. The morphology of CNC with needle-like shape, length of 672 ± 445 nm, and diameter of 103 ± 39 nm was determined by using field emission scanning electron microscopy (FESEM). The best nanocomposites performance with low CNC loading of 1 wt.% has successfully increased the tensile strength and elongation at break with 20% and 14% of improvement, respectively at 70°C of curing temperature.